The city school urdu qaida nursery (The City School Lahore, 2015)
"Urdu Qaida" is an essential textbook for learning the basics of the Urdu language, often aimed at beginners. It covers the Urdu alphabet, phonetics, simple vocabulary, and fundamental grammar rules, helping students develop their reading and writing skills in Urdu. The focus is on building a strong foundation for further language studies.